2008
DOI: 10.1007/s10654-007-9219-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neighbourhood and individual factors on injury risk in the entire Swedish population: a 12-month multilevel follow-up study

Abstract: In this cumulative incidence study of the entire population of Sweden, we examined the association between neighbourhood income level and injury risks across a comprehensive set of individual variables. The population, stratified by age (0-14, 15-64, and > or =65 years), was followed for incident injury events in 1998. Multilevel logistic regression was used to examine the associations between neighbourhood income level and injury, including deaths from injury. Risks were analyzed, taking individual demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 54 publications
4
11
0
Order By: Relevance
“…The second study, among economically active population of north-eastern France aged ≥50 years, reported prevalence of self-reported non-fatal accidents in the last 2 years of 16.5% 33 . Considering the differences in economic activity and recall periods, our data appear generally consistent with these results, although the injury mortality is known to be higher in CEE than in Western Europe or USA 1 , 4 , 5 , 34 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The second study, among economically active population of north-eastern France aged ≥50 years, reported prevalence of self-reported non-fatal accidents in the last 2 years of 16.5% 33 . Considering the differences in economic activity and recall periods, our data appear generally consistent with these results, although the injury mortality is known to be higher in CEE than in Western Europe or USA 1 , 4 , 5 , 34 …”
Section: Discussionsupporting
confidence: 82%
“…Education is frequently reported as a core social parameter predicting non-fatal injuries 4 , 34 . Somewhat surprisingly, we did not observe an inverse educational gradient in our participants.…”
Section: Discussionsupporting
confidence: 49%
“…This was not possible with the material at hand. Studies investigating the relationship between socioeconomic factors and injuries previously have shown relationships, in some cases for unspecified injuries (Owen et al 2008; Jiang et al 2007; Reading et al 1999; Faelker et al 2000; Xinjun et al 2008), whereas others have shown a relationship only with certain types of injuries (Gilbride et al 2006; Dougherty et al 1990; Reimers and Laflamme 2004; Menon et al 2008), such as fractures (Lyons et al 2000) and sports related and recreational injuries (Ni et al 2002). To reach further conclusions about the factors influencing the observed differences on the municipal level it would be of interest to direct future studies towards comparing smaller, more homogenous areas that are described in greater detail with respect to demographic, but also socioeconomic and environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…Level of neighbourhood deprivation may influence risk of childhood VI through a number of general mechanisms, including unfavourable health-related behaviours of injury [25], women during pregnancy [26,27], neighbourhood social disintegration (i.e. criminality, high mobility or unemployment) [22], it has been suggested that crime lies in the pathway linking the neighborhood social environment to poor health [28,29].…”
Section: Discussionmentioning
confidence: 99%